а) (у -4)(у + 5) = у²+5у -4у- 20=у²+у - 20
б) (х - 3) * (х² + 2х - 6) = х³ + 2х² - 6х - 3х² - 6х + 18 = х³ - х² - 12х +18
в) (3а + 2b) ( 5a - b) =15a² - 3ab + 10 ab -2b²= 15a² + 7 ab -2b²
2)
(4х+5)/6 = (3х - 2)/4 + (2х-5)/3
2(4х+5) = 3(3х - 2) + 4(2х-5)
8х + 10 = 9х - 6 + 8х - 20
8х - 17х= -26 -10
-9х= - 36
х= - 36 : (-9)
х= 4
б)
(2х+4)/3 = (5х- 2)/9 + (3х - 7)/6
6(2х+4) = 2(5х - 2) + 3(3х - 7)
12х + 24 = 10х - 4 + 9х - 21
12х - 19х= -25 - 24
-7х= - 49
х= - 49 : (-7)
х= 7
в)
(7у -4)/9 - (8-2у)/6 = (3у +3)/4
4(7у - 4) - 6(8 - 2у) = 9(3у+3)
28у - 16 - 48 + 12у = 27у +27
40у - 27у = 27 + 64
13у= 91
у = 91 : 13
у= 7